Contextualizing Community Health Practices within Islamic Legal Norms and Government Regulation: A Field-Based Inquiry from Rural Indonesia - Andika Wanda; Alamsyah Alamsyah; Eti Karini (Rule of Law Studies Journal, 2025)
Background: In remote regions of Indonesia, public health centers remain essential yet frequently struggle with service delivery challenges. Islamic legal traditions, which emphasize the protection of life and well-being, offer a complementary framework to evaluate such services alongside state-mandated regulations. Aims: This paper explores how healthcare services at the Negara Ratu Health Center comply with Indonesia’s Ministerial Regulation No. 75/2014 and investigates whether those services align with the ethical imperatives of Islamic jurisprudence. Method: Employing a qualitative case study approach, data were gathered through interviews, field observations, and documentation analysis. Participants included both healthcare providers and patients. The findings were interpreted through thematic analysis, guided by legal and religious benchmarks. Result: The study found that core aspects of the service—such as reliability and responsiveness—met regulatory expectations. However, gaps remain in areas like comfort, clarity of communication, and continuity of care. Islamic legal assessment affirmed that the services generally reflect the principles of maqashid al-shariah, especially in promoting human dignity and safeguarding health. Conclusion: Bridging state health policy with Islamic ethical values contributes to a more inclusive framework for public healthcare improvement. Targeted efforts to enhance patient satisfaction and system responsiveness are crucial in ensuring both legal compliance and moral accountability.